Caribbean countries policies for private sector development (World Bank WashingtonUS, 1994)
Identifies the main factors that constrain the private sector in the Caribbean countries. Reviews the macroeconomic and other factors that determine competitiveness. Focuses on the access of domestic and foreign competitors in Caribbean markets, and reviews the cost of doing business, including labour, capital and transaction costs.
DC